Characteristics of Post-Stroke Pain - Khairunnisah, Sitti Zhahirah; Muchsin, Achmad Harun; Mardiana, Mardiana (Journal La Medihealtico, 2024)
Stroke is a global health problem in the world as it is the leading cause of disability in adults. Stroke is a disease or functional disorder of the brain in the form of nerve paralysis caused by impaired blood flow to one part of the brain. Stroke globally ranks third in mortality after coronary heart disease (13%) and cancer (12%) in developed countries. The method used is literature review with Narrative Review design. The results obtained in this literature are that there are 8 articles obtained with restrictions from 2020 - 2023 and in-depth analysis of the strengths and limitations of each article on post-stroke pain characteristics has been carried out. 8 articles that discuss post-stroke pain characteristics, 4 articles mention post-stroke pain characteristics based on gender, 3 articles mention post-stroke pain characteristics based on pain. Based on the results of the identification and review of several in this literature review, it can be concluded that there are several characteristics of post-stroke pain including central post-stroke pain, spasticity-related pain, poststroke complex regional pain syndrome and shoulder pain. Early recognition of post-stroke pain is very important, as the prognosis will be better if the pain is treated early and aggressively.